Optimal Liability Design Under Risk and Ambiguity - Luigi Alberto Franzoni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
This paper develops an original mean-variance model able to capture the disposition of the parties towards both standard risk and ambiguity. Ambiguity arises when the causal link between conduct and harm is not univocal, as is frequently the case with toxic torts. Risk aversion and ambiguity aversion tend to have a similar impact on optimal liability rules if greater care reduces the ambiguity perceived by the parties, i.e. if safety and predictability go hand in hand. Strict liability dominates negligence when the injurer has lower degrees of risk and ambiguity aversion than the victim and can formulate less ambiguous estimates of the probability of harm. The reverse result only holds under stronger conditions.
Keywords: K13; 330